2000
DOI: 10.1021/es990979s
|View full text |Cite
|
Sign up to set email alerts
|

Principle and Process of Heavy Metal Removal from Sewage Sludge

Abstract: The sufficient removal of heavy metals from sewage sludge remains to be achieved. Heavy metals that exist on the cell surfaces of the microorganisms in the sludge seem to be dissolved by acid treatments. This study shows that heavy metals in sewage sludge can be removed easily by treating a sludge filter cake with phosphoric acid containing hydrogen peroxide for 1 h at room temperature. Phosphoric acid of 8% concentration with hydrogen peroxide showed good removal rates of heavy metals comparable to those by 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
61
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(65 citation statements)
references
References 24 publications
(22 reference statements)
1
61
0
Order By: Relevance
“…They found that at room temperature, leaching during 1 hour gave a larger release of trace metals with hydrochloric acid than with sulphuric acid. The most significant difference concerned Pb, were HCl released 100% and H 2 SO 4 just 37% of the available Pb in the sludge [10].…”
Section: Ash Extraction Procedurementioning
confidence: 97%
See 1 more Smart Citation
“…They found that at room temperature, leaching during 1 hour gave a larger release of trace metals with hydrochloric acid than with sulphuric acid. The most significant difference concerned Pb, were HCl released 100% and H 2 SO 4 just 37% of the available Pb in the sludge [10].…”
Section: Ash Extraction Procedurementioning
confidence: 97%
“…Hydrochloric acid would add chloride ions to the leachate and these could form soluble complexes with most heavy metals, thus increasing the amount of metals in solution. Yoshizaki and Tomida [10], studied removal of trace metals from sewage sludge by both hydrochloric acid and sulphuric acid in the pH-range 0.8-1.5. They found that at room temperature, leaching during 1 hour gave a larger release of trace metals with hydrochloric acid than with sulphuric acid.…”
Section: Ash Extraction Procedurementioning
confidence: 99%
“…Mercury removal from waste sewage sludge is reported [9] employing phosphoric acid as the extractant but this requires an additional step for the elution of mercury from the acid and the purification required for reusing the phosphoric acid. Precipitation method is adopted in [10] for removing lead metal from industrial effluents.…”
Section: Introductionmentioning
confidence: 99%
“…Biological acidification of the sludge is a cost-effective process for the elution of heavy metals (Blais et al, 1992;Kitada et al, 2001). Under acidic conditions, utilization of iron-oxidizing bacteria or oxidizing agents such as ferric sulfate (Fe 2 (SO 4 ) 3 ) or hydrogen peroxide (H 2 O 2 ) improved the elution efficiency of heavy metals (Ito et al, 1998;Ito et al, 2000;Yoshizaki and Tomida, 2000). Nowadays, it has been reported that heavy metal elution from the sludge or soil was promoted by the Fenton process using H 2 O 2 and ferrous sulfate (FeSO 4 ) (Dewil et al, 2007;Villa et al, 2008).…”
Section: Introductionmentioning
confidence: 99%